Westonci.ca offers quick and accurate answers to your questions. Join our community and get the insights you need today. Join our platform to connect with experts ready to provide precise answers to your questions in different areas. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.

Solve the following system of equations:

[tex]\[
\begin{array}{l}
-x - 5y = -2 \\
2x + 3y = 18
\end{array}
\][/tex]


Sagot :

To solve the given system of linear equations:

[tex]\[ \begin{array}{l} -x - 5y = -2 \quad \text{(1)} \\ 2x + 3y = 18 \quad \text{(2)} \end{array} \][/tex]

we can use the method of substitution or elimination. Here, let's use the elimination method to find the solution step-by-step.

First, we will eliminate one of the variables by making the coefficients of either [tex]\( x \)[/tex] or [tex]\( y \)[/tex] the same (or additive inverses) in both equations. Let's choose to eliminate [tex]\( x \)[/tex].

We have:
[tex]\[ -x - 5y = -2 \quad \text{(Equation 1)} \][/tex]
[tex]\[ 2x + 3y = 18 \quad \text{(Equation 2)} \][/tex]

To eliminate [tex]\( x \)[/tex], we can multiply the first equation by 2, so that the coefficients of [tex]\( x \)[/tex] in both equations are opposites:

[tex]\[ 2(-x - 5y) = 2(-2) \][/tex]

This simplifies to:
[tex]\[ -2x - 10y = -4 \quad \text{(Equation 3)} \][/tex]

Now, we can add Equation 3 to Equation 2 to eliminate [tex]\( x \)[/tex]:

[tex]\[ -2x - 10y = -4 \quad \text{(Equation 3)} \][/tex]
[tex]\[ 2x + 3y = 18 \quad \text{(Equation 2)} \][/tex]

Adding these two equations together, we get:

[tex]\[ (-2x + 2x) + (-10y + 3y) = -4 + 18 \][/tex]

This simplifies to:
[tex]\[ 0x - 7y = 14 \][/tex]

So, we have:
[tex]\[ -7y = 14 \][/tex]

Solving for [tex]\( y \)[/tex]:
[tex]\[ y = \frac{14}{-7} \][/tex]
[tex]\[ y = -2 \][/tex]

Now that we have the value of [tex]\( y \)[/tex], we can substitute it back into one of the original equations to find [tex]\( x \)[/tex]. Let's substitute [tex]\( y = -2 \)[/tex] into Equation 1:

[tex]\[ -x - 5(-2) = -2 \][/tex]

This simplifies to:
[tex]\[ -x + 10 = -2 \][/tex]

Subtracting 10 from both sides, we get:
[tex]\[ -x = -2 - 10 \][/tex]
[tex]\[ -x = -12 \][/tex]

Multiplying both sides by -1, we get:
[tex]\[ x = 12 \][/tex]

Therefore, the solution to the system of equations is:
[tex]\[ x = 12 \][/tex]
[tex]\[ y = -2 \][/tex]

So, the solution is [tex]\( (12, -2) \)[/tex].
We hope this information was helpful. Feel free to return anytime for more answers to your questions and concerns. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. We're here to help at Westonci.ca. Keep visiting for the best answers to your questions.